Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/anie.201204073
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Metallapyridyne Complex

Abstract: Building bridges: The first m-metallapyridine and the first metallapyridyne were synthesized under mild reaction conditions. The two complexes are metal-bridged polycyclic metallabenzenoid aromatics, in which the transition-metal center is shared by both six-membered rings. The synthetic method permits the use of metallabenzene as a starting material to access higher π-electron metallaaromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 65 publications
2
42
0
2
Order By: Relevance
“…The Os1=N1 bond length (1.806(10) Å) is within the typical range of bond lengths for azavinylidene–osmium complexes (1.777–1.881 Å), and the N1=C4 bond length (1.261(15) Å) is in the expected range for C=N double‐bond lengths. The Os1−C1 (2.095(11) Å) and C1=C2 (1.350(16) Å) bond lengths are similar to those found in other osmium–vinyl metallacycles and support the presence of a vinyl moiety. In contrast to the metallacycles in 2 a and 3 a , that in complex 4 a clearly deviates from planarity, which is reflected by the sum of the angles in the six‐membered ring (713.4°).…”
Section: Resultssupporting
confidence: 73%
“…The Os1=N1 bond length (1.806(10) Å) is within the typical range of bond lengths for azavinylidene–osmium complexes (1.777–1.881 Å), and the N1=C4 bond length (1.261(15) Å) is in the expected range for C=N double‐bond lengths. The Os1−C1 (2.095(11) Å) and C1=C2 (1.350(16) Å) bond lengths are similar to those found in other osmium–vinyl metallacycles and support the presence of a vinyl moiety. In contrast to the metallacycles in 2 a and 3 a , that in complex 4 a clearly deviates from planarity, which is reflected by the sum of the angles in the six‐membered ring (713.4°).…”
Section: Resultssupporting
confidence: 73%
“…采用 这种方法, 不仅可以合成具有高度热稳定性的金属杂 苯 [8] , 还可以稳定经典有机中多种重要的活性中间体, 如异苯 [9] 、苯炔 [10] 和吡啶炔 [11] . 这些金属杂环化合物在 空气氛中均具有较高的热稳定性.…”
Section: 高活性物种(如: 环内累积多烯、芳炔等)是有机反应 的重要中间体unclassified
“…虽然目前有多例金属苯炔化合物的合成报道, 但是, 金属吡啶炔一直未见报道. 我们课题组 [11] 发现在 引入金属的同时, 在主环上引入季鏻取代基, 可以有效 地稳定吡啶炔化合物(Chart 5). 有趣的是, 在化合物 12 和 13 中, 氮原子均位于金 属的间位(Chart 6, B).…”
Section: 金属吡啶炔unclassified
“…Although the isolation and study of a considerable number of metallabenzenes and fused‐ring metallabenzenes has been reported, much remains to be explored regarding the reactivity of these compounds. Studies carried out so far have demonstrated that the transition metal modifies significantly the delocalized π‐system and the chemical reactivity compared to the corresponding organic analogues . Theoretical studies have shown that the nature and position of ring substituents can have a large influence on the stability and reactivity of metallabenzenes …”
Section: Introductionmentioning
confidence: 99%